The Internet as a Research Tool for African Studies - Pasch, Helma (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
The internet has become recognized quite generally as a valuable research tool. Even though African languages are not well represented in the internet there are numerous pieces of valuable information for African Studies to be discovered in virtual fieldwork: short vocabularies and descriptions of various African languages published by individual authors, university departments or travel agencies, and texts in African languages mostly written or translated by missionaries or NGOs. These data tend to reflect the standard variants of the languages used. Contributions in forums provide, however, a type of speech that is close to oral communication. Linguistic data can be found by using the name of the respective languages combined with terms such as “language”, “grammar”, “course” or the name of an author as search items. Series of words (in double quotes) that are likely to occur in oral and/or written language constitute good search items for finding texts and contributions to forums.